The M2 macrophage marker CD206: a novel prognostic indicator for acute myeloid leukemia - Zi-Jun Xu (OncoImmunology, 2020)
Hematological malignancies possess a distinctive immunologic microenvironment compared with solid tumors. Here, using an established computational algorithm (CIBERSORT), we systematically analyzed the overall distribution of 22 tumor-infiltrating leukocyte (TIL) populations in more than 2000 bone marrow (BM) samples from 5 major hematological malignancies and healthy controls. Focusing on significantly altered TILs in acute myeloid leukemia (AML), we found that patients with AML exhibited increased frequencies of M2 macrophages, compared to either healthy controls or the other four malignancies. High infiltration of M2 macrophages was associated with poor outcome in AML. Further analysis revealed that CD206, a M2 marker gene, could faithfully reflect variation in M2 fractions and was more highly expressed in AML than normal controls. High CD206 expression predicted inferior overall survival (OS) and event-free survival (EFS) in two independent AML cohorts. Among 175 patients with intermediate-risk cytogenetics, the survival still differed greatly between low and high CD206 expressers (OS; P < .0001; 3-year rates, 56% v 32%; EFS; P < .001; 3-year rates, 47% v 25%). When analyzed in a meta-analysis, CD206 as a continuous variable showed superior predictive performance than classical prognosticators in AML (BAALC, ERG, EVI1, MN1, and WT1). In summary, M2 macrophages are preferentially enriched in AML. The M2 marker CD206 may serve as a new prognostic marker in AML.